1985
DOI: 10.1007/bf00964975
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of γ-glutamyltransferase from human brain microvessels

Abstract: Two forms of gamma-glutamyltransferase from human brain cortex microvessels were partially purified by gel permeation and ion-exchange and group-affinity chromatography. The specific activity of the purified preparations was 320-fold (detergent form) and 830-fold (proteolytic form) higher than that of the enzyme in the brain cortex homogenate. The relative molecular mass of the proteolytic form of the enzyme was about 90,000 as determined by gel permeation chromatography. The major part of the enzyme (about 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We have shown that for γ-glutamyl p-nitroanilide and glycyl glycine, in the platelets of normal subjects, the K m values were calculated as 2.1 mM and 15.9 mM respectively (Yardimci et al, 1995). It was reported in the literature that in human brain capillaries, the partially purified GGT had optimum pH between 8.2 and 9 (Vesely et al, 1985). The K m value of human liver GGT, when γ-glutamyl p-nitroanilide was used as the substrate, was reported as 1.4 mM, and for kidney it was 1.2 mM.…”
Section: Yardimci 2000)mentioning
confidence: 83%
See 2 more Smart Citations
“…We have shown that for γ-glutamyl p-nitroanilide and glycyl glycine, in the platelets of normal subjects, the K m values were calculated as 2.1 mM and 15.9 mM respectively (Yardimci et al, 1995). It was reported in the literature that in human brain capillaries, the partially purified GGT had optimum pH between 8.2 and 9 (Vesely et al, 1985). The K m value of human liver GGT, when γ-glutamyl p-nitroanilide was used as the substrate, was reported as 1.4 mM, and for kidney it was 1.2 mM.…”
Section: Yardimci 2000)mentioning
confidence: 83%
“…Purification of neutrophil GGT The method of Vesely et al (1985) was used with some modifications. Triton X-100 solubilized neutrophil fractions from nine subjects were first pooled and then precipitated with ammonium sulphate (45-90% saturation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported in the literature that L-serine (which is another essential amino acid)inhibits GGT in the presence of borate by interacting with the gamma-glutamyl binding site of the enzyme (Tate and Meister,1978;Vesely et al ,1985).GGT activity is increased in a number of primary and metastatic tumers (Dominici et al,2003). It has been shown that hepatocellular carcinoma can be expressed hepatoma specific GGT and secreted GGT in to circulating blood (Yao et al,1998).…”
Section: B Discussionmentioning
confidence: 99%